Inelastic deformation response of SDOF systems subjected to earthquakes. - Riddell, Rafael
Performance based seismic design requires reliable methods to predict earthquake demands on structures, and particularly inelastic deformations, to ensure that specific damage based criteria are met. Several methods based on the response of equivalent linear single degree of freedom (SDOF) systems have been proposed to estimate the response of multi degree of freedom structures. These methods do not offer advantages over the traditional Veletsos Newmark Hall (VNH) procedure, indeed, they have been shown to be inaccurate. In this study, the VNH method is revised, considering the inelastic response of elastoplastic, bilinear and stiffness degrading systems with 5 percent damping subjected to two sets of earthquake ground motions. One is an ensemble of 51 earthquake records in the Circumpacific Belt, and the other is a group of 44 records in California. A statistical analysis of the response data provides factors for constructing VNH inelastic spectra. Such factors show that the 'equal-displacement' and 'equal energy' rules to relate elastic and inelastic responses are unconservative for high ductilities in the acceleration and velocity sensitive regions of the spectrum. It is also shown that, on average, the effect of the type of force deformation relationship of non-linear systems is not significant and responses can be conservatively predicted using the simple elastoplastic model.
Keywords: Performance based design; Inelastic deformation; Earthquake response; Non-linear response; Inelastic spectrum